(untitled) (Journal of Comparative & International Higher Education, 2024)
This study explores the experiences of short-term study abroad faculty at a liberal arts university in the Midwestern United States. We distributed a qualitative survey to all faculty who taught short-term study abroad courses at the institution; interviewed four short-term study abroad leaders, two short-term study abroad co-leaders, and reviewed the practices and history of the institution’s study abroad office. Study participants’ experiences were consistent with role complexity and ambiguity. Role-related challenges included preparing for the program and for reentry, managing the academic side of the course, monitoring students’ and faculty members’ physical and mental health, and facilitating group dynamics. Perceived benefits included cultural enrichment, professional growth, and the ability to enhance students’ lives. Our study suggests that short-term study abroad faculty need support and professional development to prepare for their multifaceted and complex duties.